Clinically Detectable Congenital Anomalies in Newborn Babies Admitted in Neonatal Intensive Care Unit at Teaching Hospital - Suresh Kumar Meena; Rajendra Prasad Nagar (JCDR Research and Publications Pvt. Ltd., 2018)
Introduction: Any structural and chromosomal malformations can leads to significant impact on overall growth and development of a child and are among the leading cause of morbidity and mortality in newborn. Aim: To know the overall incidence of clinically detectable congenital anomaly and the types of different congenital anomaly in newborn at tertiary care hospital. Materials and Methods: All the newborn admitted in newborn intensive care unit with clinical detected congenital malformation over a period of one year. Data were recorded from medical records of admitted newborns. Results: During the study period total 9440 deliveries occurred in hospital; out of them 140 newborns were having clinically detectable malformations with Incidence of 3.6%. Mean birth weight was 2600±650 gm and mean gestational age was 36±2.8 weeks. Most common affected system was gastrointestinal (37.8%) followed by central nervous system (15%). Most common central nervous system malformations were neural tube defects. Congenital Talipus Equino Varus (CTEV) 10 (21%) was most common musculoskeletal malformation. Among all congenitally malformed patients; cleft lip and cleft palate 11 (7.8%) was most common congenital anomaly. Conclusion: Birth defects services including components of care, prevention and surveillance in the form of a well defined programme are needed in the country